Exploring language practices of immigrant mathematics teachers in multilingual grade six classrooms in South Africa - Tshabalala, Faith Lindiwe (School of Education, 2025)
Research in South African multilingual mathematics classrooms has shown that English additional language learners in the intermediate phase are mostly challenged by the fact that they have to learn mathematics in English, a language that many of them are not fluent in. To enable mathematical understanding, teachers use their own and learners' language resources, for instance, code-switching, gestures, images, and prior knowledge. But what has not been looked at is what and how immigrant teachers, who do not share a home language with Englishadditional language learners, use language practices to create opportunities for the developmentof procedural and conceptual mathematical Discourse. Thus, this study aims to describe what language practices such teachers use, and the meanings these language practices give to procedural and conceptual mathematical Discourse when performing the functions of describing mathematical procedures and concepts, asking informational questions, and clarifying these questions. The study also explores how the teachers explain their use of theselanguage practices. To achieve this aim, the study follows a social practice perspective of language, which views language as having both function and form. I use the three key language functions for teaching as identified by Pozzi, namely, describing mathematical procedures and concepts, asking informational questions, and clarifying questions. As the teachers use language practices to perform Pozzi's language functions, I look at the meanings they are building, using six of the seven building tasks from Gee, namely, activities, identities, relationships, politics, connectionsand sign systems and knowledge, with the main focus on building procedural and conceptual mathematical knowledge. I focus on three teachers from Zimbabwe, with each teacher teachinga different mathematical topic in a grade six classroom in a different school setting. The teacher from a school in an informal settlement focused on functional relationships, the teacher from the township focused on transformational geometry, and the one from a rural area focused on addition and subtraction of decimal fractions in Gauteng Province of South Africa. Data was collected through pre-observation individual interviews, classroom observation of one lesson per teacher, post-observation individual teacher interviews on language practices used in the lesson, and a focus group interview with all three teachers. Data was analyzed using Gee's method of Discourse analysis. The teacher interviews indicate that the choices of the language practices were made to enable mathematical understanding, to consider the learners' future learning in English dominant system, and to consider the immigrant teachers' positioning. Throughout their lessons, the teachers used a range of language practices such as English language, code-switching, gestures,images, formal mathematical language, informal mathematical language, learners' everyday context, previously learned mathematical concepts, decomposition, revoicing, and different forms of questions, individually and in an integrated manner. In each lesson a teacher workedto-and-fro between particular language practices, developing a pattern that connected procedural and conceptual mathematical Discourse as relevant to the mathematical topic. However, at certain moments a language practice may have worked against a teacher's intention. The teachers used some language practices more than others, depending on the functions theywere being used to perform. English language was used in most parts of the lessons by the threeteachers, in all three of Pozzi's language functions, thus building politics by making English important for building mathematical knowledge. The language practices that were mostly used to support the language function of asking informational questions were different forms of questions and revoicing. Images and gestures, which in Gee's terms refer to building sign systems, were mostly used to clarify questions. Learners' everyday contexts, previously learned mathematical concepts, decomposition, and informal mathematical language, which inGee's terms is building connections, were also mostly used to clarify questions. Code- switching to Setswana seemed to be used as a last resort to clarify questions after other languagepractices had failed, intending to build an understanding of concepts and also to build identityand relationships with the learners who did not understand English. The three teachers in my study come from the same country of origin and their motivations for using language practices are similar. However, in practice, these teachers make choices that are related to their knowledge of specific learners, the school context, the topic, their fluency in Setswana, and the home language of the learners. The Analytical Framework offers a structured tool for teacher education and professional development, helping teachers adapt language practices to build procedural and conceptual mathematical knowledge across various topics. The Framework is also adaptable for research, providing flexibility to analyze language practices and extend its use to different mathematical topics and contexts.